Atmospherics: Role of color, lighting, layout and music on consumer behaviour in a retail setting: A critical review and synthesis - Chougule, Mallika; Fukey, Leena Nitin; Sinha, Mudita (International Journal of Psychosocial Rehabilitation, 2020)
With the increasing quest to study the role and importance of atmospheric elements, the number of store atmosphere articles have dramatically been increasing in the last few years. By reviewing various articles between 1973 and 2017, this study analyses the role of color, lighting, layout and music on consumer behaviour in Retail Settings. The author summarises prior research store atmosphere research according to topicality and perspective and draws parallels between the impact of each of these elements. Overall, the role of atmospheric elements have shifted towards studying the impact of atmospheric elements.